Pengembangan Sistem Monitoring Alat (SIMA) Badan Meteorologi Klimatologi Geofisika - Rizal Mahendra; Khairul Fahmi; Sofiansyah Fadli; Wafiah Muniarti; Herin Husti Istyarini (Resolusi : Rekayasa Teknik Informatika dan Informasi, 2023)
The research was conducted at the Zainuddin Abdul Madjid Meteorological Station located in Central Lombok. The problems identified in this study were the observer officers still monitoring the Automated Weather Observer System (AWOS) one by one on the display screen in the observation room and the monitoring distance between one device and another was too far, and there was no system to display the status of each device so that it takes a long time to monitor all the tools. The purpose of this study is for observation officers to check the status of the equipment at the Zainuddin Abdul Madjid Meteorological Station and help observer officers monitor the equipment simultaneously in one view. This monitoring information system will later contain information about the equipment at the Zainuddin Abdul Madjid Meteorological Station, including information on whether or not the equipment is active, detailed specifications for the equipment, year of manufacture, year of calibration and condition of the equipment. The monitoring information system for the BMKG tool was built using the waterfall method and using the PHP programming language and MySQL as a database with system testing using a black box. The results of this study are in the form of a tool monitoring information system that can make it easier for observer officers to monitor all the existing tools at the Zainuddin Abdul Madjid Meteorological Station. And based on the results of system testing using a blackbox, all system functions are running well.